Novel lipophilic cations for delivery of mitochondria-acting therapeutics - Hu, Zhang (2018)
Mitochondria are essential cell organelles that are responsible for cellular respiration and apoptosis. Several degenerative diseases, including Parkinson’s disease, heart conditions, and cancer, have been attributed to dysfunctional mitochondria. Therefore, many efforts have been focused on the design of optimal mitochondrion-targeting drugs specifically delivered into the mitochondria. Triphenylphosphonium (TPP+) moieties are traditionally used to deliver a wide range of molecular cargo to mitochondria organelle. However, TPP+ uptake by mitochondria can result in charge accumulation, which will cause depolarisation of the mitochondrial membrane. Additionally, this type of vector cannot deliver high molecular weight cargo. It is, therefore, necessary during the design of lipophilic cation as pro-drugs and drug transporters, to investigate the factors that can minimise the therapeutic concentration and improve its delivery ability. There are two requirements for delocalized lipophilic cation to permeate mitochondrial membrane: lipophilicity and positive charge. Hence, investigating the influence of lipophilicity and charge of the molecule on its mitochondrial accumulation is necessary and critical in both scientific and medical areas. In this thesis, the author attempted to design several different lipophilicity and number of charges TPP derivatives (Chapter 2) to study the factors that affect their uptake by mitochondria through comparison of their properties (Chapter 3). Subsequently, we will investigate the improvement of the newly designed vectors for its practical application in mitochondrial therapy (Chapter 4).